Validity and Cost of Self-Study in Accreditation of Medical Laboratory Science Educational Programs. - MacPherson, Colin R. (Journal of Higher Education)
This paper reviews the validity and cost of self-study in medical laboratory science educational programs. The cost is significant, but participants have the impression that self-study is worthwhile. Objective data bearing on validity are difficult to obtain and careful studies are clearly necessary.